CONCEPTUAL FOUNDATIONS OF IMPROVING FINANCIAL REPORTING OF NONGOVERNMENTAL PENSION FUNDS - N. Gura; M. Tsybulnyk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article describes the features of the nongovernmental pension funds and accounting for them. The article defines the components of the elements of financial statements and the proposed improvement of financial reporting in the transition to international standards.